Moral intelligence and its relation to some variables A field study at the juvenile center for the delinquents in Lattakia (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research aims to identify the level of moral intelligence of juvenile delinquents in Latakia, as well as studying the differences of moral intelligence according to variables as (age, educational level of the event, marital status of the parents and the place of residence). The research was based on the descriptive approach, and its sample is consisted of (53) delinquents divided into two groups: The first is (10-15) years, the second is (16-18) years. The researcher has designed a scale of moral intelligence. The most important results of the research: a presence a low level of moral intelligence of delinquent juveniles, also differences have been appeared statistically significant in moral intelligence which are attributed to the age variable in favor of the second age group (16-18), and others due to the variable of educational level of the event in favor (secondary), In concern to the differences related to moral intelligence among sample individuals - according to marital status – the results are in favor of parents who live together, for the variable of the place of residence the differences are in favor of delinquents living in the countryside.